Factors Influencing Tourists’ Travel Experience Sharing on Social Media - Santi Novani; Retno Widiana (School of Business, IPB University (SB-IPB), 2022)
As travel-related content of tourist experiences benefits for both tourists to consume information online and for companies by providing insight into how visitors perceive their services, it becomes critical to understand the antecedents of travel experience sharing on social media. The study aims to develop a model of overall satisfaction, perceived enjoyment, motivations, and inhibitor toward sharing travel experiences, where personality factors impact overall satisfaction and perceived enjoyment. Partial Least Squares analysis was performed to evaluate the last experience of 169 Indonesian tourists in Bandung. The study discovers that conscientiousness and openness to experience trait is significant predictor of overall experience satisfaction, and only extraversion trait is identified as a significant predictor of perceived enjoyment. When it comes to predicting travel experience sharing on social media, overall satisfaction, perceived enjoyment, personal fulfillment, and self-actualization reasons have been significant predictors, but altruistic motivations and security and privacy concerns have not. Destination managers should be aware of different travelers’ personalities that could impact their satisfaction and perceived enjoyment, influencing their sharing experience behavior. Personalized service and promotion can increase contributors to sharing travel-related content on social media. Keywords: personality traits, overall satisfaction, perceived enjoyment, travel experience sharing, PLS-SEM